Diagnosis and Treatment of Secondary Hyperparathyroidism in Pre-Dialysis Stages G3-G4 Chronic Kidney Disease: A Specialized Survey in Portugal - Ferreira, Ana Carina (2024)
Introduction: The clinical management of secondary hyperparathyroidism (SHPT) in chronic kidney disease (CKD) stages G3-G4 patients currently faces several challenges. Although the understanding of SHPT has increased exponentially in recent years, many aspects regarding its diagnosis and management in non-dialysis G3-G4 CKD remain elusive. Specifically, while it is known that SHPT is linked to vitamin D insufficiency in pre-dialysis CKD patients, the target levels of vitamin D and parathyroid hormone, SHPT, and vitamin D monitoring and therapeutic guidelines are still to be clarified. It is, consequently, of utmost importance to generate data supporting consensual clinical decision-making and the implementation of evidence-based clinical practice guidelines. Methods: Thus, a single-round Delphi-like study was conducted herein to assess the opinions and the level of agreement of 59 Portuguese nephrologists on the diagnosis and treatment of pre-dialysis G3-G4 CKD patients with SHPT. Results: Although none of the statements under analysis gathered consensus, more than half of the statements regarding SHPT monitoring and therapeutics focusing on G3-G4 CKD achieved a qualified majority of agreement/disagreement. Overall, it may indicate a growing consensus trend among Portuguese nephrology specialists. Conversely, the heterogeneity of participants’ opinions regarding the treatment of SHPT-associated vitamin D insufficiency reflects the heterogeneity in the knowledge in this specific field. Conclusion: The results from this Delphi-like panel represent a first step towards improving the monitoring and therapeutic strategies concerning the prognosis of G3-G4 CKD patients, fostering unison among the Portuguese nephrology community.